Pastoral development projects. Summary of papers and discussion - International Livestock Centre for Africa (1980)
Examines basic constraints to pastoral development. Looks into project financing, design and implementation. Discusses manpower development and training procedures. Includes notes on monitoring concepts and ILCA's monitoring activities.